2010
DOI: 10.1080/00071660903421167
|View full text |Cite
|
Sign up to set email alerts
|

Multi-factorial investigation of various housing systems for laying hens

Abstract: 1. The advantages and disadvantages of various housing systems for laying hens were compared as a pilot study for work in commercial conditions. 2. At 16 weeks of age, 284 hens were introduced into one of 6 housing systems: two types of conventional cages (small: SC; large: LC), furnished cages (small: SF; large: LF), and non-cage systems (single-tiered aviary: SA; free-range: FR). 3. We evaluated the welfare, egg production, and immune response of the birds in these housing systems, built in the same location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 48 publications
4
37
0
2
Order By: Relevance
“…As a consequence there is an increase of dirty, cracked or soiled eggs (Abrahamsson and Ragnar, 1997;Huneau-Salaün et al, 2011), while no effects were observed on internal egg quality (Karaman et al, 2006). The effect of group size on performance of laying hens raises in cages with equal amount of space available per bird, as it has been studied in groups with less than 10 birds (Abrahamsson and Tauson, 1997;Shimmura et al, 2010) or with different cage models (Vits et al, 2005). Recently, there is an increasing number of studies on the effect of group size on performance of laying hens raised in cage with similar design and structures but with group sizes ranging from 8 to 60 birds (Wall, 2011;Huneau-Salaün et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence there is an increase of dirty, cracked or soiled eggs (Abrahamsson and Ragnar, 1997;Huneau-Salaün et al, 2011), while no effects were observed on internal egg quality (Karaman et al, 2006). The effect of group size on performance of laying hens raises in cages with equal amount of space available per bird, as it has been studied in groups with less than 10 birds (Abrahamsson and Tauson, 1997;Shimmura et al, 2010) or with different cage models (Vits et al, 2005). Recently, there is an increasing number of studies on the effect of group size on performance of laying hens raised in cage with similar design and structures but with group sizes ranging from 8 to 60 birds (Wall, 2011;Huneau-Salaün et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also a small number of scientific declarations that such separation is difficult. For example, the scientific declaration ‘aggressive interactions were increased by decreased litter area’ (Shimmura et al . 2007a, 2008c, 2009) cannot be separated but should be attached to one measurement: ‘litter floor’.…”
Section: Methodsmentioning
confidence: 99%
“…During construction of our model and its evaluation of the six housing systems, we assessed these housing systems using animal‐based measurement (Shimmura et al . 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to a certain degree it appears that no single housing system is ideal from a hen welfare perspective (Lay et al, 2011). Currently modern poultry industry is represented by both conventional and alternative intensive housing, which can be responsible for different health problems that are characteristic for hens kept in cages or floor, respectively (Rodenburg et al, 2005;Shimmura et al, 2010;Shini et al, 2006;Weitzenburger et al, 2005).…”
Section: Data Processing and Statistical Analysismentioning
confidence: 99%